REJUVINASI VISUAL ARSITEKTURAL BANGUNAN CANDI DIENG - Rohman, Syarifuddin; Anggrian, Mayang; Padmo Adi Nugroho , Padmo (Fakultas Ilmu Budaya, Universitas Brawijaya, 2025)
Architectural Visual Rejuvenation of Dieng Temple Buildings. This study aims to present the architectural visual rejuvenation of the Dieng Temple buildings through an illustration-based approach as an educational and cultural medium. The research is motivated by the declining collective memory of society regarding the architectural aspects and construction history of the temple, which is currently more widely recognized as a tourist destination rather than as an important historical heritage. The study employs a qualitative method through literature review, visual observation, and architectural illustration design exploration. The creative process focuses on the visual reconstruction of the form, structure, and architectural character of the temple in an informative and aesthetic manner to make it more accessible to contemporary audiences. The results indicate that architectural visualization can function as an effective medium for refreshing historical understanding and enhancing appreciation of cultural values and traditional architecture. This visual rejuvenation serves not only as an aesthetic representation but also as an interpretative tool that bridges historical knowledge, cultural context, and contemporary visual communication needs. Therefore, architectural illustration plays a significant role in preserving visual memory and strengthening cultural heritage identity.